1997
DOI: 10.1046/j.1365-2141.1997.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term stromal cultures produce dendritic‐like cells

Abstract: Summary.A stromal cell-dependent long-term culture (LTC) system has been developed from spleen which continuously generates non-adherent cells with dendritic cell (DC) characteristics. Bioassays using factor-dependent cell lines have revealed that both spleen and thymic stromal cultures secrete interleukin (IL)-3 and IL-6-like growth factors. Conditioned medium from LTC also contains factors which appear to be unrelated to IL-3 and induces growth of stromal cells from bone marrow. Non-adherent cells generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
89
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 37 publications
5
89
0
Order By: Relevance
“…It has remained constant after establishment of multiple LTC by passage of a mixture of stromal and nonadherent cells. Previous studies have shown the importance of maintaining small hemopoietic cells in LTC to perpetuate LTC-DC production (11,12). The constant presence of these two subsets within LTC suggests that they are integral to the structure and continuation of the LTC system and that the small subset may contain progenitors of the large-cell subset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has remained constant after establishment of multiple LTC by passage of a mixture of stromal and nonadherent cells. Previous studies have shown the importance of maintaining small hemopoietic cells in LTC to perpetuate LTC-DC production (11,12). The constant presence of these two subsets within LTC suggests that they are integral to the structure and continuation of the LTC system and that the small subset may contain progenitors of the large-cell subset.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenpresenting capacity of cells produced in LTC has been confirmed at numerous time points (14). LTC-DC can stimulate both allogeneic and syngeneic naive T cells as well as present antigen to antigen-specific T helper cells (11,15). In this report, surface marker expression, function, and differentiative capacity have been used to characterize two major DC subsets produced in LTC.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A constant population of cells is released into the culture supernatent and can be readily collected for analysis. Cells produced in LTC have a cell surface phenotype resembling DC with high levels of CD 1 lb, CDllc, 33D1 and CD80/CD86 (Ni & O'Neill, 1997;. Their cell surface phenotype is more consistent with myeloid DC since the great majority of cells are LTC-DC maintain the functional characteristics of DC, being endocytic (Ni & O'Neill, 1997) and highly potent APC (O'Neill et al, 1999a).…”
Section: Introductionmentioning
confidence: 88%